2017
DOI: 10.1155/2017/4927214
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition andIn VitroAntioxidant, Cytotoxic, Antimicrobial, and Larvicidal Activities of the Essential Oil ofMentha piperitaL. (Lamiaceae)

Abstract: The essential oil was obtained by hydrodistillation and the identification and quantification of components were achieved with the use of GC-MS analysis. The antioxidant activity was evaluated by the method of sequestration of DPPH. Essential oils were used for study the cytotoxic front larvae of Artemia salina. In the evaluation of the antimicrobial activity of essential oils, we employed the disk-diffusion method. The potential larvicide in mosquito larvae of the third stage of development of Aedes aegypti t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…A similar result was observed for an aqueous extract from Mentha haplocalyx when incubated with LPS-stimulated macrophages [ 26 ]. These studies and others [ 12 , 17 , 24 ] also suggested an antioxidant potential for peppermint and other plants from the same genus. We found that H 2 O 2 , but not NO production, was decreased in LHAE-treated cells stimulated with LPS at concentrations as low as 1 μ g/ml.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…A similar result was observed for an aqueous extract from Mentha haplocalyx when incubated with LPS-stimulated macrophages [ 26 ]. These studies and others [ 12 , 17 , 24 ] also suggested an antioxidant potential for peppermint and other plants from the same genus. We found that H 2 O 2 , but not NO production, was decreased in LHAE-treated cells stimulated with LPS at concentrations as low as 1 μ g/ml.…”
Section: Discussionsupporting
confidence: 53%
“…M. piperita was previously suggested to have antimicrobial activity against both Gram-negative and Gram-positive bacteria [ 12 ], in addition to presenting with antioxidant potential in vitro [ 12 , 17 , 24 ]. In vivo anti-inflammatory actions were also reported for this plant in murine models of infection and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has demonstrated that 16.385 ± 0.24 μg/ml (Ascorbic acid equivalent anti‐oxidant capacity) and 47.23 ± .0.28% DPPH radical activity. Moreover, the anti‐oxidants activates of essential oil or extracts M. × piperita has been described some in the previous literatures (Benabdallah et al, ; da Silva Ramos et al, ; Goudjil et al, ; Kratchanova et al, ; Pramila et al, ; Zheng & Wang, ). Anti‐oxidant activities are depicted in Table .…”
Section: Pharmacological Activities Of M × Piperitamentioning
confidence: 82%